2013
DOI: 10.1128/mbio.00572-12
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights into the Atopic Eczema-Associated Skin Commensal Yeast Malassezia sympodialis

Abstract: Malassezia commensal yeasts are associated with a number of skin disorders, such as atopic eczema/dermatitis and dandruff, and they also can cause systemic infections. Here we describe the 7.67-Mbp genome of Malassezia sympodialis, a species associated with atopic eczema, and contrast its genome repertoire with that of Malassezia globosa, associated with dandruff, as well as those of other closely related fungi. Ninety percent of the predicted M. sympodialis protein coding genes were experimentally verified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
211
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(226 citation statements)
references
References 108 publications
(151 reference statements)
9
211
0
1
Order By: Relevance
“…In addition to promoting genetic variation, required for adaptation to fluctuating environments and longterm survival, sexual reproduction in many fungal species, in particular, has a central role in pathogenic development (Bakkeren et al 2008;Nadal et al 2008;Heitman 2010;Heitman et al 2014). It is thus not surprising that recent advances in genome sequencing have revealed that most fungal species have retained the machinery for sexual reproduction and meiosis (Halary et al 2011;Dyer and O'Gorman 2012;Gioti et al 2013;Heitman et al 2014). However, this resilience to keep sexual competence intact comes with an extremely dynamic evolution of sexual behaviors and mating type-determining mechanisms, which may influence important evolutionary and ecological processes, such as adaptation and speciation (Billiard et al 2011;Heitman et al 2013;Nieuwenhuis et al 2013).…”
mentioning
confidence: 99%
“…In addition to promoting genetic variation, required for adaptation to fluctuating environments and longterm survival, sexual reproduction in many fungal species, in particular, has a central role in pathogenic development (Bakkeren et al 2008;Nadal et al 2008;Heitman 2010;Heitman et al 2014). It is thus not surprising that recent advances in genome sequencing have revealed that most fungal species have retained the machinery for sexual reproduction and meiosis (Halary et al 2011;Dyer and O'Gorman 2012;Gioti et al 2013;Heitman et al 2014). However, this resilience to keep sexual competence intact comes with an extremely dynamic evolution of sexual behaviors and mating type-determining mechanisms, which may influence important evolutionary and ecological processes, such as adaptation and speciation (Billiard et al 2011;Heitman et al 2013;Nieuwenhuis et al 2013).…”
mentioning
confidence: 99%
“…Also in Basidiomycota, genomes of the agent of atopic eczema, Malassezia sympodialis and that associated with dandruff, Malassezia globosa, have been compared with the expected finding in these lipophilic yeasts of no genes for fatty acid synthesis and few genes for lipid biosynthesis, and the unexpected result that there were few genes known to mediate adhesion or biofilm production in organisms that seemingly must adhere to their hosts (Gioti et al 2013). Given the role that fungi must play in allergies, an exciting aspect of the study was a focus on antigenic proteins, one of which, Mala S 7, has history of gene expansion.…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…Allergen-specific IgE against Malassezia can also be detected in children associated with their AD severity in infancy (Kekki et al 2013). Thirteen allergens have so far been identified in Malassezia (Scheynius and Crameri 2010), and at least 12 genes encoding different classes of the proteins have been confirmed to be present in both the M. sympodialis and M. globosa genomes (Gioti et al 2013). Interestingly, several of the identified allergens are proteins of unknown function with no sequence homology to characterized proteins, whereas others are homologous to host proteins, suggesting the possibility of cross-reactive immune responses.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…There are several indications that Malassezia may be sexual. A mating locus has been found in all three Malassezia genome sequences that have been reported; a population study of M. sympodialis has provided evidence for recombination; and many meiosis and mating signaling genes are present (Gioti et al 2013). However, despite repeated attempts, no one has yet demonstrated mating in Malassezia (Gioti et al 2013).…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation